Site project management record system using microsoft excel - Gan Zi Wei (School of Environmental Engineering, University Malaysia Perlis, 2013)
This research was made by using the questionnaire to get the view from the construction companies which include contractor and consultant about using the spreadsheet in construct the site diary. From this research, it can be concluded that this site diary form is better made by spreadsheet that can increase the effectiveness in the construction management and most of respondents were agreed about this.